Karakteristik Fisiko-Kimia Tepung Jagung Termodifikasi Secara Fermentasi Menggunakan Lactobacillus plantarum FNCC-0027 - Winarti, Sri; Rosida, Dedin Finatsiyatul; Febriana, Ma’faza Rizka (Jurnal Ilmu Pangan dan Hasil Pertanian, 2022)
Modified corn flour is flour produced by modifying corn to produce better flour properties. One way to modify flour is by fermentation using lactic acid bacteria (LAB). The purpose of this study was to determine the effect of granule size and fermentation time on the physico-chemical characteristics of modified corn flour using Lactobacillus plantarum FNCC-0027. This study used a completely randomized design (CRD) with a factorial pattern of 2 factors, the first factor was the size of granules (corn flour; corn rice) and the second factor was fermentation time (0; 24; 48; 72 hours) with 3 replications. The data obtained were analyzed using ANOVA, if there was a significant difference between treatments, then further tests were carried out using the DMRT test. The results showed that the best treatment was granule size in the form of flour and 72 hours of fermentation, producing modified corn flour with the following characteristics: total BAL10.09 log CFU/mL; water content 7.46%; starch content 71.88%; amylose content 27.04%; swelling power 7.68 (g/g); 3.25% solubility; and damage to the granule structure of corn starch. Modified corn flour produced has better properties than unmodified flour, including: increasing amylose content, swelling power, solubility, viscosity and reducing aflatoxin contamination. Â